Long-run post-event returns in global stock markets - Bessembinder, Hendrik; Cooper, Michael J.; Jiao, Wei; Zhang, Feng (Journal of International Business Studies, 2025)
Firms often experience significant abnormal stock returns following major corporate events, but these returns vary widely across countries. We examine how national institutions—particularly financial system development, investor protection, and governance practices—influence post-event stock returns for over 164,000 events across 58 countries. Our analysis covers six frequent corporate events: dividend initiations, share repurchases, seasoned equity offerings, stock splits, mergers and acquisitions, and initial public offerings. Using a characteristic-based benchmarking approach that accounts for cross-country differences in firm fundamentals, we find that firms in countries with more developed financial systems and stronger investor protections exhibit significantly smaller long-run post-event abnormal returns. These findings are robust to alternative benchmarks and model specifications. Our results suggest that the institutional environment can reduce informational frictions and promote more efficient investor responses to corporate announcements. In countries with strong financial and governance institutions, market reactions to corporate events are more muted—indicating fewer pricing anomalies and more efficient capital markets. By demonstrating how national institutions help shape the outcomes of firm-level events, our study highlights the value of incorporating institutional context into international finance research and helps explain why post-event return patterns often differ across countries.